Update 2011: Clinical and Genetic Issues in Familial Dilated Cardiomyopathy - Hershberger, Ray E. (2011)
A great deal of progress has recently been made in the discovery and understanding of the genetics of familial dilated cardiomyopathy (FDC). A consensus has emerged that with a new diagnosis of idiopathic dilated cardiomyopathy (IDC), the clinical screening of 1(st) degree family members will reveal FDC in at least 20-35% of cases. Point mutations in 31 autosomal and 2 X-linked genes representing diverse gene ontogeny have been implicated in causing FDC, but account for only 30-35% of genetic cause. Next generation sequencing (NGS) methods have dramatically decreased sequencing costs, making clinical genetic testing feasible for extensive panels of DCM genes. NGS also provides opportunities to discover additional genetic cause of FDC and IDC. Guidelines for evaluation and testing of FDC and IDC are now available, and when combined with FDC genetic testing and counseling will bring FDC/IDC genetics to the forefront of cardiovascular genetic medicine.